The Healthy Homes Study: Protocol for a cluster randomized trial of a place-based smoke-free home intervention in affordable housing - Mark R. Hawes; Deepalika Chakravarty; Jing Cheng; Margaret A. Handley; Janice Y. Tsoh; Tracy Kuo Lin; Robert A. Hiatt; Maya Vijayaraghavan (PLoS ONE, 2025)
Introduction Comprehensive clean air policies reduce exposure to secondhand tobacco and cannabis smoke, as well as nicotine aerosols, and improve health outcomes. However, these policies often do not apply to the eight million residents of multiunit affordable housing, many of whom are from minoritized populations. One strategy to promote smoke-free living environments is to increase the voluntary adoption of no-smoking rules in the home. Methods We describe the protocol for the Healthy Homes study—a wait-list cluster randomized controlled trial of a smoke-free home intervention for affordable housing residents. The intervention was adapted from a prior version using the Capability Opportunity Motivation-Behavior (COM-B) model and the Behavior Change Wheel. We will enroll 544 residents at 48 affordable housing sites across Northern California. Sites will be randomized to intervention or wait-list control. Resident participants will receive a one-hour coaching session on how to adopt a smoke-free home. Housing staff will be trained as lay health workers to provide brief cessation coaching. Residents and staff will complete follow-up visits at 3 and 6 months. The intervention will be delivered in English, Spanish, Chinese (Mandarin and Cantonese), and Vietnamese. The primary resident outcome is voluntary adoption of a smoke-free home for 90 days or more at 6 months. The secondary outcome is carbon monoxide–verified point prevalence tobacco abstinence. For lay health workers, the primary outcome is change in Smoking Knowledge, Attitudes, and Practices scores. We will assess cost-effectiveness and use the Consolidated Framework for Implementation Research to evaluate implementation outcomes, including characteristics of successful adopters and multilevel drivers of behavior change. Discussion Expanding access to smoke-free affordable housing is critical for reducing racial and ethnic health inequities. This study has the potential to support voluntary smoke-free home adoption, increase quitting, and reduce secondhand smoke exposure among affordable housing residents. Trial registration ClinicalTrials.gov NCT06170437